Association between arterial stiffness and left ventricular diastolic function in relation to gender and age. Issue 1 (January 2017) - Kim, Hack-Lyoung; Lim, Woo-Hyun; Seo, Jae-Bin; Chung, Woo-Young; Kim, Sang-Hyun; Kim, Myung-A.; Zo, Joo-Hee
Abstract : Abstract: Left ventricular (LV) diastolic dysfunction and subsequent overt heart failure are more prevalent in elderly women. Close interaction between arterial stiffness and LV morphology/function has been reported. The aim of this study was to investigate whether there is an age- and gender-dependent relationship between arterial stiffness and LV diastolic function. A total of 819 subjects (58.6 ± 13.3 years, 50.2% men) without structural heart disease (LV ejection fraction ≥50%) were retrospectively analyzed. All participants underwent transthoracic echocardiography and brachial-ankle pulse wave velocity (baPWV) measurement on the same day. The association of baPWV with septal e′ velocity and average E/e′ was assessed. In the total study subjects, baPWV was negatively correlated with septal e′ velocity ( r  = 0.383, P  < 0.001), and positively correlated with E/e′ ( r  = −0.266, P  < 0.001). These linear correlations remained significant even after stratificaion of the study subjects by age (<65 years vs ≥65 years) and genders ( P  < 0.05 for each). There were obvious differences in baPWV according to groups with normal LV diastolic function, intermediate profile and LV diastolic dysfunction in young ( P  = 0.010) and elderly (≥65 years) women ( P  < 0.001) and eldery men ( P  = 0.012) but not in elderly men ( P  = 0.270). There was a significant association of baPWV with septal e′ velocity ( β  = −0.258, P  = 0.020) and E/e′ ( β  = 0.122, P  = 0.030) in elderly women even after controlling for multiple clinical covariates. This independent association was not seen in younger women and men ( P  > 0.05 for each). In conclusion, baPWV was independently associated with septal e′ velocity and E/e′ in elderly women but not in younger women or men. The results of this study provide additional evidence that increased arterial stiffness plays an important role in the development of heart failure with preserved ejection fraction as well as LV diastolic dysfunction in elderly women.